2016
DOI: 10.1039/c5ra19139d
|View full text |Cite
|
Sign up to set email alerts
|

Strong, flexible and thermal-resistant CNT/polyarylacetylene nanocomposite films

Abstract: A new nanocomposite with excellent tensile strength, flexibility and heat-resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Carbon nanotubes (CNTs) are an ideal reinforcing material that are used to obtain a high-modulus and conductive polymer nanocomposite, because of their great mechanical properties, good conductivity, nanoscale diameter and high aspect ratio. [1][2][3][4][5][6][7] Previous studies have shown that CNTs have a Young's modulus of ca. 1000 GPa and a tensile strength of 10-50 GPa, which are much higher than those of conventional bres, such as carbon bers and other nanollers such as clay and silica.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon nanotubes (CNTs) are an ideal reinforcing material that are used to obtain a high-modulus and conductive polymer nanocomposite, because of their great mechanical properties, good conductivity, nanoscale diameter and high aspect ratio. [1][2][3][4][5][6][7] Previous studies have shown that CNTs have a Young's modulus of ca. 1000 GPa and a tensile strength of 10-50 GPa, which are much higher than those of conventional bres, such as carbon bers and other nanollers such as clay and silica.…”
Section: Introductionmentioning
confidence: 99%
“…So, it is necessary to use some methods such as modication, functionalization and compatibilizing of CNTs to gain a uniform dispersion of nanoparticles in the polymer matrix and promote good interfacial interaction/adhesion between the polymer matrix and nanoparticles. 3,[8][9][10] The electrical conductivity of polymer/CNT nanocomposites (PCNTs) can be increased through the formation of a ller network above the ller concentration, known as the percolation threshold. [11][12][13][14] This means that signicant conductivity of PCNTs is only obtained at or above the percolation threshold.…”
Section: Introductionmentioning
confidence: 99%
“…An important task in the creation of carbon composite materials is to increase the value of the coke residue of pyrolysates. For this reason, phenylene polymers with reactive C≡C−H groups have been proposed to be used as a binder with a high coke residue in the creation of carbon–carbon ablative materials in rocket engineering [35–38] . In addition, such polymers are good modifiers of industrial resins, increasing the coke residue of these resins during pyrolysis [39,40]…”
Section: Resultsmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) possess excellent mechanical and physical properties. [1][2][3][4][5][6] These extraordinary properties endow CNT-reinforced composites multifunctionalities for the applications of structural damping, 7,8 electrostatic discharge (ESD), 9,10 electromagnetic interference (EMI) shielding, 11,12 structural health monitoring (SHM), 13,14 and lightning strike protection. 15 However, the reinforcing effect of CNTs is still far below expectation, even less than that of carbon fibers (CFs).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with [CF/CF/CF] composite, the in-plane electrical conductivities 0 ,45 , and 90 of hybrid composite with global CNT content of 21 wt% increased to 742, 431, and 277 S cm À1 , which were enhanced by 2.6 times, and two and three orders of magnitude, respectively. The electrical conductivities of the CNT film/polyarylacetylene composite,6 MWCNT sheet/bismaleimide nanocomposite,31 and CNT film/epoxy composite with 55 wt% resin content41 were reported to be 700, 915, and 912 S cm À1 , respectively. The electrical conductivity of hybrid composites reached the same order of magnitude as CNT film composite.Figure 8(b) shows the in-plane electrical conductivities of [CF/CF/CF], [CF/CNT/CF], and [CF/E-CNT/ CF].…”
mentioning
confidence: 99%